2016
DOI: 10.1186/s13104-016-2233-x
|View full text |Cite
|
Sign up to set email alerts
|

The Danish Neuro-Oncology Registry: establishment, completeness and validity

Abstract: BackgroundThe Danish Neuro-Oncology Registry (DNOR) is a nationwide clinical cancer database that has prospectively registered data on patients with gliomas since January 2009. The purpose of this study was to describe the establishment of the DNOR and further to evaluate the database completeness of patient registration and validity of data.MethodsThe completeness of the number of patients registered in the database was evaluated in the study period from January 2009 through December 2014 by comparing cases r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…Loss to follow‐up occurs only due to emigration and was taken into account by censoring at date of emigration from the Danish Civil Registration System . Furthermore, using the nationwide Danish Neuro‐Oncology Register, which has been shown to have an overall completeness of 92% allowed us to include high quality medical data with minimal risk of bias related to retrospective recall, and with minimal selection bias compared with self‐reported data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Loss to follow‐up occurs only due to emigration and was taken into account by censoring at date of emigration from the Danish Civil Registration System . Furthermore, using the nationwide Danish Neuro‐Oncology Register, which has been shown to have an overall completeness of 92% allowed us to include high quality medical data with minimal risk of bias related to retrospective recall, and with minimal selection bias compared with self‐reported data.…”
Section: Discussionmentioning
confidence: 99%
“…Information on glioma patients' disease characteristics was obtained from the Danish Neuro‐Oncology Register, which, since 2009, has registered all cases of histologically and surgically verified glioma . Disease characteristics included Eastern Cooperative Oncology Group performance status (0–1, 2, ≥3) before surgery or, if unavailable, after surgery, grade (WHO I and II, III and IV), longest‐lasting symptom (neurological deficit, seizure, cognitive symptoms, headache, or other), epilepsy at onset (yes, no), and treatment (surgery, surgery and chemotherapy, surgery and radiation, or surgery, chemotherapy, and radiation).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Quality control occurs at three levels; as part of central validation e.g., for personal identifiers and hospital codes, as part of the administrative curation of data at the registry organizations, e.g., for dates and missing data, performed by the RKKP, the CRN and the RCCs and as part of quality control studies of core variables. Most cancer-related clinical registries have completeness rates exceeding 95% when compared to registered diagnoses in the national cancer registries and in patient-administrative systems (Table 3) [14][15][16][17][18][19][20][21][22][23][24][25][26]. Differences in diagnostic criteria and alternative treatment routes may explain missed inclusion in the clinical registries.…”
Section: Clinical Variables and Data Qualitymentioning
confidence: 99%
“…Validation studies are crucial to improve data quality and detect differences in coding systems and algorithms and incompatibilities between different data sources. In the Swedish registries for gynecologic cancer, breast cancer, prostate cancer and gastro-esophageal cancer validation studies focused on core variables in 400-800 patients have shown 82-91% agreement on individual data point level, which demonstrates a need for continuous quality assurance initiatives [17,20,[24][25][26].…”
Section: Clinical Variables and Data Qualitymentioning
confidence: 99%